Implementasi Model Inquiry dengan Media Film Animasi dalam Pembelajaran Menulis Teks Ulasan - Hutagalung, Yossi Anatasya; Sitorus, P. Jamaluddin; Panggabean, Sarma (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to analyze the results of the implementation of the Inquiry model with Animated Film Media in Learning to Write Review Texts. This research was carried out in SMA Negeri I in class XI. The sampling technique was carried out by simple cluster sampling. The sampling technique was divided into two groups, namely the experimental class group of 30 students and the control class as many as 30 students, in order to obtain a total sample of 60 students. Ink's research used a two group posttest experimental design. To obtain the data used the assignment of writing a review text. From the analysis, the students' ability to write review texts in class XI of SMA Negeri I Pegajahan without using animated film media obtained the lowest score of 50 and the highest score of 87, with an average score of 63.5. The ability of students to write review texts in class XI of SMA Negeri I Pegajahan using animated film media obtained the lowest score of 60 and the highest score of 89, with an average of 72.23. Based on the results of the calculations, it was obtained that tcount = 3.757 and ttable = 2.042 with a significant level of 0.05 indicating tcount > ttable, then the alternative hypothesis (Ha) was accepted. In conclusion, the use of the inquiry model with animated film media affects the ability of students to write review texts for class XI students of SMA Negeri I Pegajahan. Keywords: Inquiry Model, Animated Film Media, Learning, Review Text